Maintaining and caring for the manuscripts of the Prophet’s biography and using them in the historical studies - Al–Leheabi, Saleh Muhammad Zeki Mahmood (Al-Adab Journal, 2021)
This research sheds light on the manuscripts of the Prophet’s biography and the efforts made to care for them, whether through institutions or scholars and individuals, it also shows their historical and scientific significance and their impact on the studies. The importance of the research is that it focuses on a selected collection of manuscripts of the Prophet’s biography that are located in several libraries in different countries, and what are the methods and measures taken to maintain them, with an explanation and details of models of the Prophet’s biography manuscripts. It is evident through the research that the manuscripts of the Prophet’s biography, like many sources of our heritage, suffer from lack of unification of efforts in the process of taking care of these manuscripts, especially in the field of study and investigation, where the shortage is still largely occurring. We also see the ability of many orientalists to accomplish several works that contributed to maintaining, investigating, and bringing to light those manuscripts, in a way that sometimes exceeds what Muslim researchers have done, which calls for encouraging and directing focuses to achieve better results. The research shows that the manuscripts of the Prophet’s biography were in many forms, like independent manuscripts, single, combined, included and other forms, all of which based on the style of writing used in authorship and the motives behind writing of the books of the Prophet’s biography and finally is the historical stage in which they were written.